The effect of disaggregated country risk on foreign portfolio investment flows in South Africa - Muzindutsi, Paul-Francois (Economic and business review, 2025)
This study explores the relationship between disaggregated country risk and foreign portfolio investment (FPI) flows in South Africa, focusing on both the long-run and short-run effects of economic, financial, and political country risk measures on net foreign purchases of shares (NFPS) and net foreign purchases of bonds (NFPB) during the period from 1995 to 2019. We employed autoregressive distributed lag (ARDL) and nonlinear autoregressive distributed lag (NARDL) models to assess the relationships between the variables. The results indicate that all disaggregated country risk measures have a long-run effect on NFPS and NFPB, and the impacts of these risks are asymmetric. Specifically, low levels of economic risk are associated with a decline in foreign equity flows and an increase in foreign bond investments in the long run, while high levels of economic risk correlate with a rise in both foreign equity and bond investment flows. Conversely, both high and low levels of financial and political risk lead to a decrease in NFPS and NFPB. Notably, financial risk was the only country risk measure found to significantly impact NFPB in the short run. The findings highlight the importance for policymakers to understand these complex relationships in order to implement strategies that foster a mutually beneficial economic, political, and financial climate in South Africa, encouraging FPI while maintaining sovereignty.
Keywords: country risk; deželno tveganje; economic policy; ekonomska politika; investicije; investments; Južna Afrika; South Africa